2001
DOI: 10.1038/35081000
|View full text |Cite
|
Sign up to set email alerts
|

The four final rotation states of Venus

Abstract: Venus rotates very slowly on its axis in a retrograde direction, opposite to that of most other bodies in the Solar System. To explain this peculiar observation, it has been generally believed that in the past its rotational axis was itself rotated to 180 degrees as a result of core-mantle friction inside the planet, together with atmospheric tides. But such a change has to assume a high initial obliquity (the angle between the planet's equator and the plane of the orbital motion). Chaotic evolution, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 23 publications
8
124
0
Order By: Relevance
“…Atmospheric thermal tides can result in an equilibrium rotation period that is different from the synchronized one (Correia et al 2008). This is for instance at the origin of the current rotation state of Venus (Correia & Laskar 2001). Therefore, assuming a synchronized planet may not be consistent with a dense atmosphere.…”
Section: Nonsynchronized Planetsmentioning
confidence: 99%
“…Atmospheric thermal tides can result in an equilibrium rotation period that is different from the synchronized one (Correia et al 2008). This is for instance at the origin of the current rotation state of Venus (Correia & Laskar 2001). Therefore, assuming a synchronized planet may not be consistent with a dense atmosphere.…”
Section: Nonsynchronized Planetsmentioning
confidence: 99%
“…There have already been many studies on the rotation of Venus. Several authors have studied this rotation on a long time scale to understand why Venus' spin is retrograde and why its spin axis has low obliquity (Goldstein 1964;Carpenter 1964;Goldreich & Peale 1970;Lago & Cazenave 1979;Dobrovoskis 1980;Yoder 1995;Correia & Laskar 2001, 2003. Others studied the possible resonance between the Earth and Venus (Gold & Soter 1979;Bills 2005;Bazsó et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…If that occurred, the torque from Earth could dominate and spin-lock Venus to the Earth (Gold and Soter, 1969). More recent and detailed work has shown that this interaction can be significant and permits chaotic spin evolution that eventually settles into one of four possible states (Correia and Laskar, 2001). Although a large atmosphere can play a significant role in the evolution of terrestrial planets (Correia and Laskar, 2003), we ignore their effect here due to the large number of unknowns for an exoplanet.…”
Section: E4 Tidal Response In Celestial Bodiesmentioning
confidence: 99%